IMPRESI IKLIM ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING DI DINAS KEBUDAYAAN KABUPATEN BULELENG: Impression Of Organizational Climate On Employee Job Satisfaction Through Work Mitivation As An Intervening Variabel In The Buleleng Regency Cultural Service - Noval, I Made Mai; Devi, Komang Elma Triana (Ganec Swara, 2025)
This the aim of this research is to analyze how organizational atmosphere influences job fulfillment via motivational mediation in the Cultural Department of Buleleng. The analytical method employed includes assessing the measurement model, evaluating the structural path, and testing assumptions testing, using the SEM-PLS application, 2025.The results of this study indicate that organizational climate has a positive and significant relationship with employee job satisfaction, with this it can be said that the better the organizational climate, the greater the job satisfaction at the Buleleng Regency Cultural Service. Organizational climate has a positive and significant relationship to increasing employee motivation, so it can be said that the better the organizational climate, the more work motivation will increase at the Buleleng Regency Cultural Service. Work drive shows a meaningful and favorable relationship with increasing workforce happiness; thus, enhanced job drive leads to greater fulfillment will increase at the Buleleng Regency Cultural Service. The test results on the parameter coefficients between the effect of corporate environment on worker fulfillment through motivational mediation show a positive influence with an the base coefficient is 0.178, t-value is 2.123, and p-value 0.005; indicating a meaningful and favorable effect influence.